Distribution of allelic and genotyping frequency of A1/A2 allele of beta casein in Badri cattle - Aashaq Hussain Dar; Sanjay Kumar; Parvesh Kumari; M Mukesh; DV Singh; RK Sharma; AK Ghosh; Balwinder Singh; Vijay Amrit Panwar; Monika Sodhi (Journal of Livestock Biodiversity, 2025)
Beta caseins (13-casein), the major milk protein, has two most important variants A1 and A2. A1 milk is considered as potential contributor to some of the important human diseases like diabetes and cardiovascular diseases. The present study was undertaken to explore the existing 13-casein A1/A2 polymorphism in Badri cattle from Uttarakhand state of India using PCR-RFLP approach. A high frequency of A2 allele (0.88) was observed in Badri cattle with genotypic frequency for A2A2 and A1A2 to be 0.76 and 0.24 respectively. The analysis indicates that the Badri cattle is a good resource for A2 milk like other indigenous cattle breeds of India.